Correlation Between Symptom Clusters and Quality of Life in Children With Acute Leukemia During Chemotherapy. Issue 2 (20th March 2022) - Li, Rongrong; Yao, Wenying; Chan, Yuying; Shen, Min; Wang, Xin; Wen, Fang; Yang, Qi
Abstract : Background: Children with acute leukemia experience various distressing symptoms due to the disease and its treatment during chemotherapy. These symptoms cluster together and have negative impacts on patient outcomes. Objective: The aim of this study was to examine symptom clusters that children with acute leukemia undergoing chemotherapy are experiencing and the impact of these symptom clusters on their quality of life. Methods: A cross-sectional study design was used, and 184 Chinese children with acute leukemia who were undergoing chemotherapy were invited to participate in the study. Memorial Symptom Assessment Scale 10–18 and Pediatric Quality of Life Inventory General Core Module version 4.0 were applied. Exploratory factor analysis and multiple regression were used to identify symptom clusters and their influence on the quality of life. Results: Six symptom clusters were identified as gastrointestinal, emotional, neurological, skin mucosal, self-image disorder, and somatic cluster. The severity of each symptom cluster was negatively correlated with quality of life. Among them, gastrointestinal, emotional, and somatic clusters were significant predictors of quality of life. Conclusions: There are multiple symptom clusters in children with acute leukemia, which seriously affect children's quality of life. To relieve symptom burden and improve quality of life, nursing and medical staff should pay attention to the symptom management and control in a symptom cluster perspective. Implications for Practice: The results of this study will provide suggestions for the healthcare provider to plan for these symptoms and manage any concurrent symptoms for the successful promotion of children's quality of life.